Effectiveness of Phoenix Dactylifera and Oxytocin Massage on Prolactin Levels in Breastfeeding Mothers in Palembang City - Aprilina, Aprilina; Ocktariyana, Ocktariyana; Lestari, Dian (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Exclusive breastfeeding is essential in the growth and development of babies and improves maternal health. Exclusive breastfeeding can reduce infant mortality rates; of the 3 thousand infant deaths in Indonesia, 10 million deaths of children aged less than 5 years in the world each year can be prevented by exclusive breastfeeding. The hormones that play a role in breastfeeding mothers are prolactin and oxytocin. The research aimed to look at the effectiveness of oxytocin massage and Phoenix dactylifera in increasing the levels of the hormone prolactin in breastfeeding mothers. The research was a Quasi Experiment with a Post Test only design, a sample of 30 people divided into three groups. Phoenix Dactylifera intervention, oxytocin massage intervention, and control without treatment. The research was conducted at TPMB Palembang city. Analysis using the Shapiro-Wilks test for data homogeneity using Levene's test (pmore than 0.05) and the One Way ANOVA test compared the means of the three groups. The results showed no significant differences between the three groups where the ρ value was more than 0.05. The conclusion is that there is nothing more effective in increasing prolactin hormone levels than giving Phoenix dactylifera and oxytocin massage because it is thought to be caused by many influencing factors, including age, education, nutritional intake, and maternal parity.